Pengelolaan Kebun Kakao Rakyat pada Kelompok Tani Wanita Bundo Saiyo, Tarantang Kecamatan Harau, Kabupaten Lima Puluh Kota - Erlinda, Rita; Noveri, Noveri; Fajri, Fajri; Situmorang, Helentina; Fitri, Elva Rahmi; Amir, Syafri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Cocoa is a plantation crop that is widely cultivated by the community in the Tarantang district, Harau District, both in the form of